If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -36 = 2y Reorder the terms: -36 + 3y = 2y Solving -36 + 3y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -36 + 3y + -2y = 2y + -2y Combine like terms: 3y + -2y = 1y -36 + 1y = 2y + -2y Combine like terms: 2y + -2y = 0 -36 + 1y = 0 Add '36' to each side of the equation. -36 + 36 + 1y = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 1y = 0 + 36 1y = 0 + 36 Combine like terms: 0 + 36 = 36 1y = 36 Divide each side by '1'. y = 36 Simplifying y = 36
| -28=7n | | 3/16.8 | | 2m=6m-20 | | -61=-48+c | | -.25x+3.5=-.625 | | -2(5+2r)=-6-5r | | 1/3x-3=-2 | | (3-z)(3z+4)=0 | | 81x^2-27x-18=0 | | 94=t+6 | | T^3-12t^2+45t+2=0 | | 6y+7/5 | | 4x+6y=-30 | | 5(b+1)=2(b-5) | | 5u(u-8)(u-6)=0 | | 5a-8whena=9 | | 5b+5=2b-10 | | 3x+15=57 | | y-79=-61 | | -(1+5n)=-4n | | 2x+4y=122 | | 73-6x=3x+23 | | 2x+19=-79-9x | | 2x+19=-19-9x | | -57+r=66 | | 63+w=92 | | -3pie+w=2pie | | 9-8x=30-22x | | -20-5x=5-10 | | 22=46+b | | 64+48v+9v^2=0 | | -13-17x=9x+19 |